2022
DOI: 10.3390/antibiotics11101451
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in the Discovery and Design of Antimicrobial Peptides Using Traditional Machine Learning and Deep Learning

Abstract: Antimicrobial resistance has become a critical global health problem due to the abuse of conventional antibiotics and the rise of multi-drug-resistant microbes. Antimicrobial peptides (AMPs) are a group of natural peptides that show promise as next-generation antibiotics due to their low toxicity to the host, broad spectrum of biological activity, including antibacterial, antifungal, antiviral, and anti-parasitic activities, and great therapeutic potential, such as anticancer, anti-inflammatory, etc. Most impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 223 publications
0
34
0
Order By: Relevance
“…On the contrary, antibacterial peptide materials are less susceptible to drug resistance due to their different mechanisms of action and their chemical–physical features. Unfortunately, the production of natural antibacterial peptides still falls in the realm of high‐cost compounds with significant production times concerning the expectancies of high clinical demand (Yan et al, 2022 ). Thus, optimization of their pharmacokinetic and pharmacodynamic characteristics is necessary for the design and synthesis of new feasible antibiotic candidates.…”
Section: Applicationsmentioning
confidence: 99%
“…On the contrary, antibacterial peptide materials are less susceptible to drug resistance due to their different mechanisms of action and their chemical–physical features. Unfortunately, the production of natural antibacterial peptides still falls in the realm of high‐cost compounds with significant production times concerning the expectancies of high clinical demand (Yan et al, 2022 ). Thus, optimization of their pharmacokinetic and pharmacodynamic characteristics is necessary for the design and synthesis of new feasible antibiotic candidates.…”
Section: Applicationsmentioning
confidence: 99%
“…Experimental results showed that 181 of the 216 identified candidate AMPs showed antimicrobial activity (positive rate of >83%). For a comprehensive review of MLenabled AMP discovery and design, we refer readers to the review by Yan et al 50 Other In a recent study, Rios-Martinez et al pioneered the usage of a self-supervised neural network masked language model called BiGCARP 54 that contains the ByteNet encoder-dilated CNN architecture 55 with linear input embedding and outputdecoding layers for predicting and classifying BGCs from microbial genomes. Trained on 127,000 BGC sequences represented as ESM-1b-pretrained embeddings of a protein family domain, 56 BiGCARP can capture meaningful patterns in BGCs with area under the receiver operating characteristic (AUROC) scores ranging from 0.936 to 0.950 and outperforms DeepBGC on classifying four out of seven product classes.…”
Section: ■ Ml-assisted Genome Mining Of Npsmentioning
confidence: 99%
“…The inclusion of AMPs in device coatings has also been proposed to combat infection. These compounds, described as next-generation antibiotics because they are far less susceptible to the development of pathogen resistance compared to conventional antibiotics, are potent and exhibit rapid and broad-spectrum antibacterial activity [ 112 , 113 ]. AMPs play a key role in natural defence mechanisms and have been isolated from various natural sources including bacteria, fungi, viruses, plants, and animals.…”
Section: Antimicrobials and Anti-biofilm Strategiesmentioning
confidence: 99%